2011
DOI: 10.1073/pnas.1110889108
|View full text |Cite
|
Sign up to set email alerts
|

Distant Mimivirus relative with a larger genome highlights the fundamental features of Megaviridae

Abstract: Mimivirus, a DNA virus infecting acanthamoeba, was for a long time the largest known virus both in terms of particle size and gene content. Its genome encodes 979 proteins, including the first four aminoacyl tRNA synthetases (ArgRS, CysRS, MetRS, and TyrRS) ever found outside of cellular organisms. The discovery that Mimivirus encoded trademark cellular functions prompted a wealth of theoretical studies revisiting the concept of virus and associated large DNA viruses with the emergence of early eukaryotes. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
337
1
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(357 citation statements)
references
References 32 publications
16
337
1
3
Order By: Relevance
“…Indeed, we have previously shown that the mimivirus collagen-like protein L71 is hydroxylated and glycosylated in vitro by the L230 enzyme (17). Structurally related proteins are also found in related giant viruses, such as megavirus (Arslan et al 2011) and moumouvirus (Yoosuf et al 2012), which also include collagen genes in their genome. Considering their stability and activity when expressed in E. coli, proteins from giant viruses may represent a valuable source of enzymes for biotechnological applications, as shown here for the production of hydroxylated recombinant collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have previously shown that the mimivirus collagen-like protein L71 is hydroxylated and glycosylated in vitro by the L230 enzyme (17). Structurally related proteins are also found in related giant viruses, such as megavirus (Arslan et al 2011) and moumouvirus (Yoosuf et al 2012), which also include collagen genes in their genome. Considering their stability and activity when expressed in E. coli, proteins from giant viruses may represent a valuable source of enzymes for biotechnological applications, as shown here for the production of hydroxylated recombinant collagen.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, to escape criticism Raoult shifted from a metabolist view, to a purely geneticist view, to something undefined in between, thus adding even more confusion to the debate. Claverie changed his opinion to say that giant viruses are degenerated cells (Arslan et al 2011). This implies that these viruses would not constitute a fourth domain on the same footing as cellular domains, as previously claimed, because now they would derive from within a cellular domain.…”
Section: Do Some Giant Viruses Form a Fourth Domain Of Life?mentioning
confidence: 96%
“…The claim for a fourth domain of life was specifically made for the giant Mimivirus and related nucleo-cytoplasmic large DNA viruses (NCLDV), which have very large genomes. Some of these genomes exceed the size of some parasitic bacterial genomes and possess some homologues to cellular genes involved in typical cellular processes including translation (Arslan et al 2011;Boyer et al 2009;Raoult et al 2004;Van Etten 2011). Based on simple phylogenetic analyses, the viral homologues of those cellular genes branched at the base of eukaryotes, which was taken as evidence of this viral family forming a fourth domain of life that could be placed in a universal tree of cellular organisms using shared genes (Boyer et al 2010;Raoult et al 2004).…”
Section: Novel Virocentric Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The long lasting debate about the position of viruses in the great divide between the living and nonliving has been only intensified in recent years with the discovery of viruses with huge genomes that encode proteins which allow for mechanisms that we do associate with life [9][10][11]. These gigantic viruses are more complex than some bacteria which even further obscures the question of their status and their origin.…”
Section: Introductionmentioning
confidence: 99%